PENGARUH PEMBERIAN KUDAPAN TERHADAP STATUS GIZI DAN STATUS ANEMI SISWA SDN PASANGGRAHAN 2 PURWAKARTA (The effect of snack intervention on student nutritional and anemia status at Pasanggrahan 2 elementary school, Purwakarta District) - Ikeu Tanziha; Gita Prasojo; Irawati Rahmawati; Maharani -; Dwi Rusmawati (EKOLOGIA, 2013)
The objective of this study was to analyze the effect of snack intervention on student nutritional and anemia status at Pasanggrahan 2 elementary school. Design study was experimental onegroup pretest-postest design and was conducted at Pasanggrahan 2 elementary school in Purwakarta from August to December 2012. The total number of fifty three students were selected purposively. The primery data were collected namely: household social economi and student characteritics, food habbit, nutritional and anemia status. The result of study showed that the energy and protein contribution to average of students nutrition adequate was 17.9% and 23.6% respectively. While the contribution of snack energy and protein to average of daily total nutrition consumption was 26.7% and 31.3% respectively. There was significant difference of student nutritional and anemia status before and after snack intervention as additional school feeding.